Firms' Margins of Adjustment to Wage Growth: The Case of Italian Collective Bargaining - Francesco Devicienti; Bernardo Fanfani (Institute of Labor Economics (IZA), 2021)
This paper studies firms' adjustment behavior to the growth in labor costs induced by Italian collective bargaining institutions. Our research design compares several firms' outcomes across collective agreements within the same sector and geographic location, exploiting discontinuities in contractual wages' growth as a source of variation in labor costs. Results show that on average employment and revenues fall, wages increase, while firms' productivity, workers' average quality, the profit margin and capital intensity do not change in response to higher labor costs. These effects are heterogeneous across the firms' productivity distribution. Employment, revenues, productivity and the profit margin are positively or not related to contractual wage growth among relatively more efficient firms, while they are negatively related to this shock at less productive companies. More efficient firms tend to substitute high- with low-skilled workers, which are instead more likely to be laid off by less efficient employers. These results suggest that more efficient companies adjust to the growth in labor costs through cost-saving strategies and they may benefit from cleansing effects that increase their product market shares.
Keywords: J00; J23; J24; J31; J38; J58; L13; 330; collective bargaining; minimum wage; productivity; employment; matched employer-employee data